ҚАРАҚАЛПАҚ ДӘСТАНЛАРЫНЫҢ ИЗЕРТЛЕНИЎ МӘСЕЛЕЛЕРИ («Юсуп-Ахмет» дәстаны мысалында) - Жаксымова, У.Ж. (FAN va JAMIYAT, 2019)
The article is devoted to the study of the level of research of an epos «Yusup-Akhmet», its national-aesthetic sources and historical roots.